Mechanisms of Action of Probiotics. (5th February 2019) - Plaza-Diaz, Julio; Ruiz-Ojeda, Francisco Javier; Gil-Campos, Mercedes; Gil, Angel
ABSTRACT: Probiotics are living microorganisms that confer health benefits to the host when administered in adequate amounts; however, dead bacteria and their components can also exhibit probiotic properties. Bifidobacterium and strains of lactic acid bacteria are the most widely used bacteria that exhibit probiotic properties and are included in many functional foods and dietary supplements. Probiotics have been shown to prevent and ameliorate the course of digestive disorders such as acute, nosocomial, and antibiotic-associated diarrhea; allergic disorders such as atopic dermatitis (eczema) and allergic rhinitis in infants; and Clostridium difficile –associated diarrhea and some inflammatory bowel disorders in adults. In addition, probiotics may be of interest as coadjuvants in the treatment of metabolic disorders, including obesity, metabolic syndrome, nonalcoholic fatty liver disease, and type 2 diabetes. However, the mechanisms of action of probiotics, which are diverse, heterogeneous, and strain specific, have received little attention. Thus, the aim of the present work was to review the main mechanisms of action of probiotics, including colonization and normalization of perturbed intestinal microbial communities in children and adults; competitive exclusion of pathogens and bacteriocin production; modulation of fecal enzymatic activities associated with the metabolization of biliary salts and inactivation of carcinogens and other xenobiotics; production of short-chain and branched-chain fatty acids, which, in turn, have wide effects not only in the intestine but also in peripheral tissues via interactions with short-chain fatty acid receptors, modulating mainly tissue insulin sensitivity; cell adhesion and mucin production; modulation of the immune system, which results mainly in the differentiation of T-regulatory cells and upregulation of anti-inflammatory cytokines and growth factors, i.e., interleukin-10 and transforming growth factor; and interaction with the brain-gut axis by regulation of endocrine and neurologic functions. Further research to elucidate the precise molecular mechanisms of action of probiotics is warranted.